Characteristics and factors associated with antihypertensive medication use in patients attending peruvian health facilities - Mejia, Christian R. (2017)
Introduction Hypertension is a very common disease worldwide, and medication is needed to prevent its short-term and long-term complications. Our objective was to determine the characteristics and factors associated with antihypertensive medication use in patients attending Peruvian health facilities. Materials & Methods We performed a multicenter, cross-sectional study with secondary data. We obtained self-reported antihypertensive medication from patients attending health facilities in 10 departments of Peru. We looked for associations of the antihypertensive treatment according to sociopathological factors and obtained p values using generalized linear models. Results Of the 894 patients with hypertension, 61% (547) were women and 60% (503) were on antihypertensive treatment, of which 82% (389) had monotherapy and 52% (258) had recently taken their medication. Antihypertensive treatment was positively correlated with the patient's age (adjusted prevalence ratio [aPR]: 1.01; 95% confidence interval [CI]: 1.007 to 1.017; p value < 0.001), diabetes (aPR: 1.31; 95% CI: 1.11 to 1.55; p value = 0.001) and cardiovascular disease (aPR: 1.38; 95% CI: 1.26 to 1.51; p value < 0.001). Conversely, the frequency of antihypertensive treatment decreases with physical activity (aPR: 0.80; 95% CI: 0.70 to 0.92; p value = 0.001). Conclusion Patients who have comorbidities and advanced age are more likely to be on antihypertensive treatment. In contrast, patients with increased physical activity have a lower frequency of antihypertensive treatment. It is important to consider these factors for future preventive programs and to improve therapeutic compliance.